Daily synoptic conditions associated with large fire occurrence in Mediterranean France: evidence for a wind‐driven fire regime. (19th February 2016) - Ruffault, J.; Moron, V.; Trigo, R. M.; Curt, T.
ABSTRACT: Changes in wildfire activity in the Mediterranean area over recent decades increase the need for a better understanding of the fire–weather relationships and for the development of reliable models to improve fire danger prediction. This study analyses daily synoptic and local weather conditions associated with the occurrence of summer large fires (LFs) in Mediterranean France during recent decades (1973–2013). The links between large fire occurrence and synoptic conditions are analysed with composites of sea level pressure and winds at 925 hPa and a parsimonious synoptic weather type (WT) classification based on these variables. A cluster analysis is used to identify five homogeneous regions with similar inter‐annual variations in fire activity. Our results reveal a dominant wind‐driven fire regime, i.e. wind conditions are the main factor explaining why fire become large, though substantial temporal and spatial variations are observed. Thus, most LFs occur under the ' Atlantic Ridge ' WT that combines an anticyclonic ridge over eastern Atlantic and a cyclonic anomaly stretched from the North Sea to Central/Eastern Europe and Mediterranean basin. This pattern is significantly related at local scale to fast continental dry winds. By contrast, only few LFs occur under WTs characterized by anomalously warm local‐scale conditions (' Blocking '), except under very warm and dry conditions such as during the outstanding 2003 summer. These results offer promising developments for the improvement of fire danger predictions and operational management.